IMPLEMENTASI PENYELENGGARAAN OTONOMI DAERAH DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT - Sunardi, Sunardi; Nur Syafiq, Ahmad; Hernanda, Trias (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2024)
Regional autonomy, introduced during the reform era, aims to grant broader and greater authority to local governments to manage their respective regions based on local needs. Although the regional autonomy policy has been implemented for more than 20 years, its application remains uneven. This is due to various challenges, such as corruption and conflicts of authority. This study employs a qualitative method with a normative juridical approach. The findings of this research indicate that decentralization within regional autonomy provides significant opportunities to improve public services and the Human Development Index. However, this requires support in the form of good governance, effective oversight, and collaboration between the central and local governments. Keywords: Regional Autonomy, Welfare, Society